2018
DOI: 10.1007/s40617-018-0237-9
|View full text |Cite
|
Sign up to set email alerts
|

Board Certified Behavior Analysts and Psychotropic Medications: Slipshod Training, Inconsistent Involvement, and Reason for Hope

Abstract: People with autism spectrum disorder often receive psychotropic medications and two drugs, risperidone and aripiprazole, are approved for treating "irritability" in this population. A number of authors have suggested that behavior analysts can contribute to the prudent use of such drugs, but little is known regarding Board Certified Behavior Analysts' involvement in practices relevant to the use of psychotropic drugs. We e-mailed Board Certified Behavior Analysts an anonymous web-based survey regarding such pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 27 publications
0
9
0
Order By: Relevance
“…It should be noted that pharmacological treatment is conducted frequently with this population but decisions about medication are often based on clinical judgement without objective outcome measures (Poling et al, 2017 ; Spencer et al, 2013 ). Further, the combined effects from behavioral-pharmacological intervention can be difficult to assess without controlled analysis (Li & Poling, 2018 ; Matson & Dempsey, 2008 ). Establishing a system of data-informed and coordinated decision making about psychotropic medications is built on the expertise of multiple disciplines and defining standards of care for children and their families.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It should be noted that pharmacological treatment is conducted frequently with this population but decisions about medication are often based on clinical judgement without objective outcome measures (Poling et al, 2017 ; Spencer et al, 2013 ). Further, the combined effects from behavioral-pharmacological intervention can be difficult to assess without controlled analysis (Li & Poling, 2018 ; Matson & Dempsey, 2008 ). Establishing a system of data-informed and coordinated decision making about psychotropic medications is built on the expertise of multiple disciplines and defining standards of care for children and their families.…”
Section: Discussionmentioning
confidence: 99%
“…These results suggest that some prescription practices may be guided by reasonable criteria but more objective methods should be considered. For example, Li and Poling ( 2018 ) posited that applied behavior analysis (ABA) principles and methods “are often appropriate for the everyday evaluation of psychotropic medications” (p. 3). Further, behavior measurement and evaluation should be integrated within interdisciplinary teams responsible for the care and treatment of children with ASD in human services settings (Brodhead, 2015 ) especially in the context of medication management (Newhouse-Oisten et al, 2017 ).…”
mentioning
confidence: 99%
“…For example, the behavior analyst may report having sufficient competence and generally high confidence but find that the highly controlled experimental conditions differ significantly from the classroom in which services are provided. Similarly, the behavior analyst may realize the current consumer would have been excluded from relevant studies because of a comorbidity or potential side effects from psychotropic medications (Li & Poling, 2018), bringing into question the extent to which the evidence applies in the current case (Slocum et al, 2014). Under these conditions, the answer to Question 4 may be medium or low because the significant adaptations from the research conditions to the real-world application may require additional consultation or professional development.…”
Section: Framework For Self-evaluation: the Competence And Confidence Checklistmentioning
confidence: 99%
“…This means BCBAs are highly likely to be supporting clients taking psychotropic medications. In fact, in a recent survey study 40% of BCBA respondents reported that over half of the clients on their caseload were taking psychotropic medications (Li & Poling, 2018). Unfortunately, approximately 70% of BCBAs reported they either rarely or never work directly with prescribing professionals.…”
mentioning
confidence: 99%